Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-52174-w
|View full text |Cite
|
Sign up to set email alerts
|

Rapid maturation of the hepatic cell line Huh7 via CDK inhibition for PXR dependent CYP450 metabolism and induction

Abstract: CYP3A4, a cytochrome P450 enzyme regulated by the nuclear receptor PXR, is involved in most of the drug metabolizing pathways. Studying the regulation/induction of CYP3A4 and PXR is critical in toxicology and drug-drug interaction (DDI) studies. Primary human hepatocytes constitute the preferred in vitro platform for drug development efforts. However, they are expensive, scarce and heterogeneous. Hepatic cell lines, such as Huh7, could provide a cost-effective alternative, however, they express negligible amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Hepatoma-derived cell lines are commonly used to investigate NAFLD in vitro and include HepG2, Huh7, and HepaRG cells. However, these exhibit an abnormal genotype, lack population diversity, and demonstrate poor liver-specific metabolic competence causing these cell lines to be an insufficient choice in modeling CYP450 drug regulation [ 2 , 22 , 23 ]. In contrast, primary human hepatocytes (PHHs) exhibit high functionality relative to the human organ in vivo and are considered reliable for predictive toxicological and pharmacological results [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatoma-derived cell lines are commonly used to investigate NAFLD in vitro and include HepG2, Huh7, and HepaRG cells. However, these exhibit an abnormal genotype, lack population diversity, and demonstrate poor liver-specific metabolic competence causing these cell lines to be an insufficient choice in modeling CYP450 drug regulation [ 2 , 22 , 23 ]. In contrast, primary human hepatocytes (PHHs) exhibit high functionality relative to the human organ in vivo and are considered reliable for predictive toxicological and pharmacological results [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis raised was that CDK2 phosphorylated Ser-350 to attenuate PXR to activate the CYP3A4 gene; therefore, CDK2 repression resulted in Ser-350 dephosphorylation and restored PXR's ability to activate the gene in confluent Huh-7 cells. A phosphorylation-mimicking PXR S350D mutant was unable to heterocomplex with RXRa and activate the CYP3A4 promoter (55,98). Consistent with this hypothesis, treatment with a CDK inhibitor up-regulated CYP3A4 expression (98).…”
Section: Lbd Phosphorylationmentioning
confidence: 59%
“…A phosphorylation-mimicking PXR S350D mutant was unable to heterocomplex with RXRa and activate the CYP3A4 promoter (55,98). Consistent with this hypothesis, treatment with a CDK inhibitor up-regulated CYP3A4 expression (98). Moreover, a phos-phorylation-mimicking single mutation of Ser-350 to Asp disabled PXR induction of drug-metabolizing enzymes in mouse livers (99).…”
Section: Lbd Phosphorylationmentioning
confidence: 70%
“…Notably, while hPXR is DMD-MR-2022-000859-R1 one of only 5 human nuclear receptors (out of a total of 48) that does not preserve a Thr-38 like phosphorylation motif in the DBD, several phosphorylation residues including have been identified with many of them located within the LBD (Lin et al, 2008;Pondugula et al, 2009;Elias et al, 2014;Hu et al, 2020). Studies have shown that these residues could be phosphorylated by kinases such as cyclin-dependent kinase 2 (CDK2), PKA, PKC, and vaccinia related kinase 1 (VRK1); and phosphomimetic mutation of T57D and S350D markedly impaired hPXR-mediated CYP3A4 transactivation (Lin et al, 2008;Gotoh et al, 2017;Bulutoglu et al, 2019). Together, these results characterize PXR as another nuclear receptor that is regulated through both phosphorylation signaling and traditional ligand binding.…”
Section: Mechanisms Of Pb Activation Of Hpxrmentioning
confidence: 99%